The Effectiveness of Using the Listening Triangle Strategy on Improving the Critical Listening Skills among the Secondary First Grade Male Students in Libya (Abhat Journal, 2024)
This study aimed at investigating the effectiveness of using the Listening Triangle strategy on improving Critical Listening skills among the secondary first grade male students in Libya. The study used a semi- experimental design. Therefore, a sample from the first-grade male students consisting of (64) was chosen randomly from Wad dan boys' secondary school, and distributed into two equally groups; one is experimental was taught using the listening triangle strategy, and the controlled group which was taught using a traditional strategy. The researcher prepared the critical listening test of (30) items which was applied pre and post the experiment. For data analysis, Arithmetical means, Standard deviations, and ANCOVA were used. The study findings reveled that there were statically significant differences (α = 0.05) in the critical listening skills between the two groups in favor of the experimental group.
Keywords: The Listening Triangle Strategy; The Critical Listening Skills; secondary first grade male students.